lt(x->1) (x^x-x)/(x-(1+log x))

2 years ago


Answers : (3)



2 years ago

apply lhospitalno second thought

2 years ago

Is it 2

2 years ago

Post Your Answer

More Questions On Algebra

Ask Experts

Have any Question? Ask Experts
Post Question
Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details
a,b belong to N and a>1. p is prime .ax^2+bx+c=p for 2 distict integral values of x then the number of integral roots of ax^2+bx+c=2p?
Hello student, Please find the answer to your question below If a = b = N, then the roots of ax^2 + ax + c - p are -1/2 sqrt(1 - 4(c - p)/a)/2 which implies 1 - 4(c - p)/a is an odd square =...
Let m, n be the two integer valued roots of the quadratic ax 2 +bx+c-p = 0, so that ax 2 +bx+(c-p) = a (x-m)(x-n) . Let x=N be an integer such that aN 2 +bN+(c-p) = p, then a(N-m)(N-n) = p....
mycroft holmes 2 months ago
Hello student, Please find the answer to your question below. we can find the answer to this question simply by expanding the given equation (A+B) 2 =(A+B)(A+B) =A 2 +AB+BA+B 2 =A 2 +2AB+B 2
At what values of 'a' do all the zeroes of the function, f(x) = (a-2)x 2 + 2ax + a + 3 lie on the interval (-2, 1)?
Hi, You need to consider 2 cases here. Case 1 : Take a-2>0 Now the concavity is upwards, draw the desired graph and think about the conditions. We need f(-2)>0 f(1)>0 \ But this is...
Yash Baheti one month ago
The answer includes {2} . But leading coeff. is not equal to 0. Am i right ???
piyush soni one month ago
see attachment and explain it
f(x) = (x^2 + 1) / (x^4 +1) divided num & den by x^2 f(x) = (1 + 1/x^2 ) / (x^2 + 1/x^2) put x – 1/x = t = > 1 + 1/x^2 dx = dt & x^2 + 1/x^2 = (x – 1/x)^2 + 2 = t^2 + 2 ∫(x^2 + 1) / (x^4 +1)...
Y RAJYALAKSHMI 2 months ago
A ray of light coming from the point (1,2) is reflected at a point A on the x-axis and then passes through the point (5,3). What are the co-ordinates of point A?
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
Arun Kumar 3 months ago
Prove that
let y = f(x) g(x) Taking log on both sides log y= g(x) log(f(x)) Taking antilog on both sides y = e g(x) logf(x) Consider log f(x)= log ( 1 + (f(x)-1)) Expansion of log ( 1 + x)= x – x...
Harsh Patodia 13 days ago
Hi Student, Basically subtraction of 1 comes from the derivation. So it must be done. If you want to know the derivation please reply on this thread otherwise its not necessary. You can...
Harsh Patodia 14 days ago
Hi student This is of the type f(x) g(x) which is of form 1 such that f(x) 1 and g(x) Solution of such form is give by e g(x)(f(x)-1) When you will subsitute appropriate values of f(x) and...
Harsh Patodia 15 days ago
View all Questions »